Geneza i funkcje marki - ewolucja roli marki w działaniach podmiotów gospodarczych - Wrona, Sylwia (The Genesis and Function of Brand's - the Brand's Importance in Activity of Enterprises, 2008)
Recently observed vast fascination of a brand, number of books, publishings, dissertations as well as symposiums devoted to, might have suggested, that the history of a brand has been counted since merely couple, maybe dozen of years. Well, there is nothing more wrong than this belief. A brand is not an icon of modem economy, it is much older and its rudiments reach as far as ancient ages. The following article focuses on the brand's (trademark) importance evolution in activity of enterprises. It discusses the origin of the analysed category and describes how over ages product branding system has been changing and how its functionality has been developing.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 107-120